1996
DOI: 10.1021/ac960009c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Purge-and-Trap for Measurement of Volatile Organic Compounds in Aged Soils

Abstract: The U.S. EPA-recommended method for measurement of trace levels of volatile organic compounds (VOCs) in soil, purge-and-trap, measures the readily desorbable organic contaminants from soil pore spaces and external soil surfaces. It does not, however, measure contamination that has diffused into internal micropores of soil matrix. Thus, the purge-and-trap method measures only a small fraction of total soil contaminants, especially in long-contaminated soils, where ∼90-99% of contamination may be in the interior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…It has been also reported that the extraction efficiencies of methanol depends on the octanol-water partition of VOCs, soil organic carbon content as well as duration of methanol extraction. Although, elevated temperatures speed up the release of VOCs especially high octanol-water partitioning compounds from soil with high organic content, 1 day MeOH extraction was long enough to get maximum release of tested compounds used in this study and was much longer than that of hot MeOH extraction at 40 • C in an ultrasonic water bath for 30 min [18].…”
Section: Column Experimentsmentioning
confidence: 95%
“…It has been also reported that the extraction efficiencies of methanol depends on the octanol-water partition of VOCs, soil organic carbon content as well as duration of methanol extraction. Although, elevated temperatures speed up the release of VOCs especially high octanol-water partitioning compounds from soil with high organic content, 1 day MeOH extraction was long enough to get maximum release of tested compounds used in this study and was much longer than that of hot MeOH extraction at 40 • C in an ultrasonic water bath for 30 min [18].…”
Section: Column Experimentsmentioning
confidence: 95%
“…The purge and trap (P&T) method for the analysis of VOCs has been widely described in the literature. [6][7][8][9] Solid phase microextraction, SPME, despite its name, is not only another useful extraction tool, but is an innovative and complete sample preparation technique, which was first developed in 1989 by Pawliszyn and his group.…”
Section: Received 15 July 1999; Revised 1 September 1999; Accepted 2 mentioning
confidence: 99%
“…Both methods are not useful for volatile contaminants that have diffused into internal micropores of soil (the usual case for sites that were contaminated for a long time) and/or are strongly sorbed by the matrix [8,9]. In the investigations reported in this article, soil samples were obtained from a site where the VOC contamination has been in the ground for a few decades, so aging had to be considered an important factor.…”
Section: Introductionmentioning
confidence: 99%